The prognostic value of weight and body composition changes in patients with non‐small‐cell lung cancer treated with nivolumab. Issue 3 (5th May 2021) - Degens, Juliette H.R.J.; Dingemans, Anne‐Marie C.; Willemsen, Anna C.H.; Gietema, Hester A.; Hurkmans, Daan P.; Aerts, Joachim G.; Hendriks, Lizza E.L.; Schols, Annemie M.W.J.
Abstract: Background: It is not well known to what extent effectiveness of treatment with immune checkpoint inhibitors in stage IV non‐small‐cell lung cancer (NSCLC) is influenced by weight loss and changes in body composition. Therefore, the goal of this study was to evaluate body composition changes in relation to early weight change and overall survival (OS) in stage IV NSCLC patients treated with second‐line nivolumab. Methods: All patients with stage IV NSCLC, who were treated with second‐line nivolumab between June 2015 and December 2018 at Maastricht University Medical Center, were evaluated. Skeletal muscle mass (SMM), visceral adipose tissue (VAT), and subcutaneous adipose tissue (SAT) were assessed at the first lumbar level on computed tomography images obtained before initiation of nivolumab and at week 6 of treatment. The contribution of changes in body weight (defined as >2% loss), SMM, VAT, and SAT to OS was analysed by Kaplan–Meier method and adjusted for clinical confounders in a Cox regression analysis. The results from the study cohort were validated in another Dutch cohort from Erasmus Medical Center, Rotterdam. Results: One hundred and six patients were included in the study cohort. Loss of body weight of >2% at week 6 was an independent predictor for poor OS (hazard ratio 2.39, 95% confidence interval 1.51–3.79, P < 0.001) when adjusted for gender, >1 organ with metastasis, pretreatment hypoalbumenaemia, and pretreatment elevated C‐reactive protein. The result was confirmed in the validation cohort (N = 62). Loss of SMM as a feature of cancer cachexia did not significantly predict OS in both cohorts. Significant (>2%) weight loss during treatment was reflected by a significant loss of VAT and SAT, while loss of SMM was comparable between weight‐stable and weight‐losing patients. Conclusions: Weight loss, characterized by loss of subcutaneous and visceral adipose tissues, at week 6 of treatment with nivolumab, is a significant poor prognostic factor for survival in patients with Stage IV NSCLC.